Reading strategies for effective reading comprehension - Du Plooy, Annelie (Potchefstroom University for Christian Higher Education, 1995)
Ineffective reading takes place if the reader does not understand what he reads. Therefore it is important for everybody to be able to make sense of what they read. Teachers often do not pay enough attention to the teaching of comprehension in schools. Reading comprehension is an aspect that has been the least adequately explained arid therefore it is the most difficult one to teach. Even students think of it as only another exercise of English and rush through it just to finish as soon as possible. Teachers hand back the exercises and give the correct answers without instructing students on how to improve their comprehension. By teaching students different reading strategies their proficiency in comprehension may improve. Most of the students are unaware of reading strategies and they don't know how to implement them in their comprehension.- This study offers an empirical investigation into the teaching of four specific reading strategies to students in an attempt to help them to improve their reading comprehension. The literature on language learning strategies and reading strategies, as well as the teaching and learning of reading strategies, is surveyed. The results of an empirical investigation into the teaching of four reading strategies (guessing the meaning of the word from the context, finding the main idea in a passage, making inferences and generalizing) indicate that, although there was only a marginal improvement in reading comprehension, it is clear that the teaching of reading strategies has enormous potential. English Second Language teachers may find it worth their while to implement the teaching of reading strategies to develop their students' proficiency in reading comprehension.
Thesis (MEd (Vakdidaktiek))--PU vir CHO, 1996
Keywords: Reading comprehension; Reading strategies; Learning strategies; Language learning strategies